The moral economists : R.H. Tawney, Karl Polanyi, E.P. Thompson, and the critique of capitalism - Rogan, Tim, 1983- (Princeton University Press, 2017)
A fresh look at how three important twentieth-century British thinkers viewed capitalism through a moral rather than material lens What's wrong with capitalism? Answers to that question today focus on material inequality. Led by economists and conducted in utilitarian terms, the critique of capitalism in the twenty-first century is primarily concerned with disparities in income and wealth. It was not always so. The Moral Economists reconstructs another critical tradition, developed across the twentieth century in Britain, in which material deprivation was less important than moral or spiritual desolation. Tim Rogan focuses on three of the twentieth century's most influential critics of capitalism--R.H. Tawney, Karl Polanyi, and E.P. Thompson. Making arguments about the relationships between economics and ethics in modernity, their works commanded wide readerships, shaped research agendas, and influenced public opinion. Rejecting the social philosophy of laissez-faire but fearing authoritarianism, these writers sought out forms of social solidarity closer than individualism admitted but freer than collectivism allowed. They discovered such solidarities while teaching economics, history, and literature to workers in the north of England and elsewhere. They wrote histories of capitalism to make these solidarities articulate. They used makeshift languages of "tradition" and "custom" to describe them until Thompson patented the idea of the "moral economy."